Current trends of the organization of work and human resource management to improve productivity in industrial enterprises - A. M. Belyaev; I. A. Kovaleva (Путеводитель предпринимателя, 2020)
Solution of actual problem of continuous improvement in productivity as a key indicator of staff efficiency of the industrial enterprise is achieved through integrated application of all elements of the organization of work in designing work process and adopting special measures to improve productivity. The efficiency of human resource management is due to the allocation of the key role of the employee and the application of modern methods of organization and behavior of production processes, with an emphasis on the rational organization ofworkplaces and the need for the management training.